Epistemic modality, language, and conceptualization : a cognitive-pragmatic perspective - Nuyts, Jan (Human cognitive processing, 2001)
The relationship between language and conceptualization remains one of the major puzzles in language research. This monograph addresses this issue by means of an in depth corpus based and experimental investigation of the major types of expressions of epistemic modality in Dutch, German and English. By adopting a systematic functional orientation, the book explains a whole range of peculiarities of epistemic expression forms (synchronically and diachronically), and it offers a clear perspective on which cognitive systems are needed to get from the concept of epistemic modality to its linguisti.